Diametral theory of algebraic surfaces and geometric theory of invariants of groups generated by reflections. III - Ignatenko, V. F. (Ukrains’kyi Matematychnyi Zhurnal, 1998)
We present the geometric theory of invariants of wild groups of skew symmetries in a real Euclidean space.